An unusual long standing tracheal foreign body in a paediatric patient removed via tracheostome: A case report - Saitabau, Zephania; Mrisho, Baraka Emmanuel; Swai, Henry; Ntunaguzi, Daudi; Massawe, Enica Richard (Indian Journal of Case Reports, 2019)
Aspirated foreign bodies are commonly reported in pediatric patients and accounts for emergencies. A long standing undiagnosed foreign body (FB) in the trachea is very rare and lethal and the diagnosis needs a high index of suspicion. Foreign bodies in the trachea are uncommon and usually present with acute respiratory symptoms sometimes mimicking bronchial asthma. A long standing tracheal FB is a rare presentation.We report a 4-year old female child who presented with a history suggestive of FB inhalation about 2 years’ prior admission. She was treated in several health facilities as a case of bronchial asthma/pneumonia with no clear relief. This case highlights the role of clinicians in having a high index of suspicion when encountering children with unresolving pneumonia so as to rule out the possibility of foreign body inhalation.